Moldova Mobile ID Case Study - World Bank (World Bank, Washington, DC, 2019)
The Republic of Moldova was among the first countries in the world to implement Mobile eID, whichhas been implemented through the innovative Public-Private Partnership (PPP) model. In recognitionof Moldova embracing mobile technologies as an opportunity to tap the potential of mobile phones toimprove government initiatives, the government of Moldova was awarded the Best mGovernment Awardby the GSMA during the 2013 Mobile World Congress in Barcelona. The concept of Mobile eID, also known as mobile signature, works as an ID in the virtual world, allowing users to authenticate themselves in cyberspace, with the aim to prove their identity with the help of a cell phone or electronically sign a legally-binding transaction or document. For the regular users, the advantage of mobile eID lies in its simplicity, since no separate card reader or drivers areneeded, as the phone itself already performs these functions. Implementation of Mobile eID in Moldova was part of a larger digital transformation initiative supported by a 20 million US Dollars World Bank–funded loan as part of Governance eTransformation Project (GeT), and assuch, it benefited from increased political support. Moreover, the approval by the government of Moldova of the strategic e-Transformation program further paved the way for eID implementation, by expressly stating that mobile electronic identity is "a means to ensure data integrity and security in eservice delivery and financial transactions."